Uruguay : Report on Observance of Standards and Codes-Data Module and the Response by the Authorities. (IMF Staff Country Reports; Country Report ;, 2001)
The paper provides a summary of Uruguay's practices with respect to the coverage, periodicity, and timeliness of the Special Data Dissemination Standard (SDDS) data categories, and an assessment of the quality of national accounts, prices, fiscal, monetary and financial, and external sector statistics. Uruguay has made good progress recently in improving the dissemination of statistical information. The Internet pages of the Central Bank of Uruguay (BCU) and the National Institute of Statistics (INE) allow increasingly detailed monitoring of developments in the Uruguayan economy.